Influential Article Review - Creating a Platform for Open Innovation and the Growth of Production Mechanisms - Ryan, Mitchell; Floyd, Roy; Austin, Eunice (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation and operations. We present insights from a highly influential paper. Here are the highlights from this paper: Innovation is the engine of development for enterprises, and there is an increasing trend to adopt an open innovation strategy. However, how to manage external resources in an open, collaborative and complementary manner, and in a shared environment that will yield the greatest networking effects, it is a challenging task. Because there is no such a satisfactory model for an open innovation strategy that combine operational mechanisms with the management of, external resources. Thhis article tries to fill the gap by adopting a resource-based perspective to construct an overall open innovation (OOI) business model. In this model, external resources are classified as industrial and non-industrial entities, to enable the identification of the interaction methods between manufacturing enterprises and external resources. The management of external resources involved in a Technology Open Innovation (TOI) cycle is given particular attention that includes: 1) the classification of the external resources of a TOI, 2) the general mechanisms extracted to promote qualified resources in and unqualified resources out, and 3) a business model to conceptualize the collaboration between enterprises and external resources. A case study of TOI is also provided to empirically verify its feasibility. This paper contributes to the literature by providing an original operational model and mechanism design for an open innovation strategy that can manage external resources effectively. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.